Personality of individually housed dairy-beef crossbred calves is related to performance and behavior - Michalski, Emily; Woodrum Setser, Megan M.; Mazon, Gustavo; Neave, Heather W.; Costa, Joao H. C. (Frontiers in Animal Science, 2023)
The aim of this study was to evaluate differences in behavioral responses of individually housed dairy-beef crossbred calves to standardized personality tests (novel person, novel object, and startle test) and investigate associations of personality traits with performance and home pen behavior. Dairy-beef crossbred (Holstein x Angus) calves (n=29) were individually housed with ad libitum access to water and calf starter. Body weight was measured weekly and calf starter intake was recorded daily from day of arrival (8.5 ± 2.1; experimental day 1) for 76 days. Behavior within the home pen (eating, drinking, non-nutritive oral manipulation) and activity were recorded on experimental days 13, 32, 53, and 67 using a camera and a pedometer. The calves were subjected to standardized personality tests in their home pen at the end of the experimental period (80.7 ± 2.0 d of age), including a novel person test (stationary person in the corner of their home pen) and combined novel object/startle test (remote-controlled car in the pen, that suddenly moved when touched). A principal component analysis on the behaviors recorded from the tests (latency to approach person or object, time spent attentive and touching the person or object, and time spent inactive, playing and grooming) yielded 3 factors that explained 76.1% of the variance, and were interpreted as personality traits labeled “fearful”, “inactive”, and “bold”. These factors were examined in regression analyses for their associations with home pen behavior and performance. The factor “fearful” had negative associations with total average daily gain and average grain intake. In contrast, the factor “inactive” had positive associations with non-nutritive oral manipulation of buckets or walls. The factor “bold” had no significant association with any of the performance or home pen behavior measures. In conclusion, personality traits identified from standardized tests were related to performance and home pen behavior measures in individually housed, crossbred calves. These results complement work in group housed calves suggesting personality testing may be useful selective tools to identify high and low performing calves from an early age.